2018
DOI: 10.1108/ijoem-07-2017-0235
|View full text |Cite
|
Sign up to set email alerts
|

Influence of religious beliefs and spirituality on decision to insure

Abstract: Purpose The purpose of this paper is to examine the influence of the level of religious beliefs and individual spirituality of small business owners on their decision to insure. Design/methodology/approach Small business owners from India were asked about their perceptions regarding the relationship between their level of religious beliefs and spirituality and their decision to insure. Findings The results of this study show that the level of religious beliefs and individual spirituality of small business … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 46 publications
(41 reference statements)
1
12
0
3
Order By: Relevance
“…Kakar and Shukla (2010) found that households engaged in the financial activity of either purchasing jewellery and durable products or investing in the financial market, instead of borrowing money from the market, have a high propensity to own LIP. Gill et al (2018) pointed out that religious belief is associated with the consumer's risk-taking behaviour and is positively correlated to the LIPD of the small business owner. Similarly, the author identified a positive correlation between consumers' spirituality and their decision to insure.…”
Section: Behaviour-related Antecedentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kakar and Shukla (2010) found that households engaged in the financial activity of either purchasing jewellery and durable products or investing in the financial market, instead of borrowing money from the market, have a high propensity to own LIP. Gill et al (2018) pointed out that religious belief is associated with the consumer's risk-taking behaviour and is positively correlated to the LIPD of the small business owner. Similarly, the author identified a positive correlation between consumers' spirituality and their decision to insure.…”
Section: Behaviour-related Antecedentsmentioning
confidence: 99%
“…Similarly, the author identified a positive correlation between consumers' spirituality and their decision to insure. As religious belief derives consumer's spirituality, both the antecedents are examined to have a positive effect on LIPD (Gill et al, 2018).…”
Section: Behaviour-related Antecedentsmentioning
confidence: 99%
“…The research by Liu and Wang and Li et al showed that enhancing social medical care could significantly increase the demands of residents on commercial health insurance ( 22 , 23 ). In the research by Gill et al and Li et al, it was discovered that participating in commercial health insurance could significantly improve the health status of residents ( 23 , 24 ).…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%
“…Spirituality is the ultimate level of intelligence without any religious bias to help one understand self. Although some literature argues that SQ is about religiosity (Crisp, 2018;Gill, Mand, Biger, & Mathur, 2018;Petrosko & Alagaraja, 2017), quite some studies have however attempted to show the positive effects of religiosity in managing conflict or as a research strategy in management. For instance, Shaikh (2018) argues that although there is a mutual co-existence of both empirical knowledge (science) and religion, only religiosity can be the arbiter of moral, philosophical, political and social matters.…”
Section: Growing Importance Of Spiritual Intelligence At Workmentioning
confidence: 99%